Non-pharmacological methods of treatment and prevention of vasovagal syncope - Aleksandra Białkowska; Dariusz Dziarkowski; Szymon Gawrych; Blanka Budziejko; Oliwia Cywińska; Daria Kurtyka; Gracjan Różański; Anna Maria Dobosiewicz; Nataliia Badiuk (Kazimierz Wielki University, 2018)
Fainting is a transient loss of consciousness resulting from a momentary ischemia of the central nervous system. One type of syncope is vasovagal syncope, otherwise known as reflex or neurogenic syncope. The consequence of fainting may be a fallen injury. It is therefore important that the doctor intervene quickly after such an episode to determine the cause of the fainting. An interview, which is one of the most important parts of diagnosis, provides a lot of valuable information. Once the correct diagnosis has been made, it is important to start the treatment procedure. In the case of vasovagal syncope, the first step is to educate the patient and his family about how to deal with the condition, which causes such a reaction of the body. The patient must know the manoeuvres that will interrupt the fainting. Next, the patient is recommended to be physically active, e.g. moderate exercise, tilt training. If the non-pharmacological methods do not produce results, pharmacology is introduced, and if it also fails, the use of stimulators is recommended. Non-pharmacological methods, which are the first to be used in a given case, as well as non-pharmacological methods are the subject of research of many scientists. This article describes methods of non-pharmacological management of vasovagal syncope, which can be used by anyone suffering from this condition as non-invasive.